Pendaftaran Peralihan Hak Atas Tanah Yang Bersumber Dari Kesepakatan Ahli Waris Yang Dibuat Dihadapan Notaris - Takarub, Kukuh Derajat; Lubis, Muhammad Yamin; Sembiring, Rosnidar; Suprayitno, Suprayitno (Mahesa Research Center, 2023)
This research aims to explore in-depth the registration of the transfer of inheritance rights sourced from an agreement among heirs made before a notary. However, the registration of the transfer of rights, according to Article 37 of Government Regulation No. 24 of 1997 on Land Registration, can only be registered if proven by a deed made by a land deed official (PPAT). Consequently, there is a discrepancy in implementing the inheritance transfer according to Article 111 paragraph 3 of Regulation of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency No. 16 of 2021, which can be made in the form of an underhand deed by all heirs witnessed by 2 (two) witnesses or by a deed of inheritance division made before a notary. This research is classified as normative, and the data is analyzed qualitatively. The results indicate that an agreement is a crucial element in an agreement, where Article 1320 of the Civil Code emphasizes that an agreement is a requirement for the validity of an agreement. The agreement related to the inheritance object carried out by the parties can override what is regulated in inheritance law as long as it meets the elements of Article 1338 and does not violate Article 1321 of the Civil Code. To make the agreement a perfect evidence, it should be made before a notary with a notarial deed as referred to in Article 1870 of the Civil Code.